Experimental characterization of the oscillatory behavior of a quasi-two-dimensional collapsible channel. (October 2016) - Anderson, Peter; Fels, Sidney; Green, Sheldon
Abstract: Experiments are performed for a rigid, high-aspect-ratio, rectangular channel with a portion of one wall replaced by a flexible membrane (a "2D" Starling resistor). The fluid is air, which is driven by a pressure drop up to 300 Pa, producing Reynolds numbers up to 22, 000. The experiments include pressure measurements at 6 locations along the channel, 1 velocity measurement, and high speed video of the membrane which is analyzed to extract the membrane motion. The primary variables considered are membrane tension, inlet pressure, and area of the side-wall gap. Steady and unsteady behaviors are observed for the 3 membrane tensions considered. The unsteady behaviors are categorized as "traveling", "mode 2", or "complex" oscillations, which may be recognized by the spectral characteristics of their pressure signal. Hysteresis is clearly observed depending on how the inlet pressure is adjusted. The side-wall gap, which permits air leakage around the membrane, is an important factor, and is characterized as a function of membrane tension and inlet pressure. Abstract : Highlights: Fluid–solid interaction of quasi-2D collapsible channel characterized experimentally. Steady and unsteady FSI regimes are classified visually and by spectral content. Illustrates effect of tension, inlet pressure, and air leakage on global behaviors.